Chemotherapy versus chemoradiotherapy following surgery and neoadjuvant chemotherapy for resectable gastric cancer (CRITICS): an editorial - Wong, Joyce (Digestive Medicine Research, 2018)
Gastric cancer is a malignancy with a strong global distribution, being more common in Asian countries like Japan and South Korea. As such, treatment algorithms differ significantly between the Eastern countries and Western. According to the Japanese Gastric Cancer Guidelines, neoadjuvant therapy is not utilized, even for advanced stage cancers (1).